2020
DOI: 10.26434/chemrxiv.12593429
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Novel Fidaxomicin Antibiotics through Site-Selective Catalysis

Abstract: <div><div><div><p>Fidaxomicin (FDX) is a marketed antibiotic for the treatment Clostridium difficile infections (CDI). Although showing interesting antibacterial properties against many Gram-positive bacteria, the application of this antibiotic is currently limited to treatment of CDI. Semisynthetic modifications present a promising strategy to improve its pharmacokinetic properties and also circumvent resistance development by broadening the structural diversity of derivatives.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Over the last decades, the understanding of the relevant biological pathways and targets for antibiotic activity has been significantly expanded. Historically, activity on the bacterial target was most importantly optimized and has been constantly improved by molecular design, [1][2][3] synthetic chemistry, [3][4][5] and analytical techniques up to recently introduced cryo EM structure determination. 6 Less studied but equally important, several additional factors strongly contribute to overall antibiotic performance, including bacterial uptake of antibiotics, their biotransformation to inactive substances, the active efflux of those agents by bacteria, and others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last decades, the understanding of the relevant biological pathways and targets for antibiotic activity has been significantly expanded. Historically, activity on the bacterial target was most importantly optimized and has been constantly improved by molecular design, [1][2][3] synthetic chemistry, [3][4][5] and analytical techniques up to recently introduced cryo EM structure determination. 6 Less studied but equally important, several additional factors strongly contribute to overall antibiotic performance, including bacterial uptake of antibiotics, their biotransformation to inactive substances, the active efflux of those agents by bacteria, and others.…”
Section: Introductionmentioning
confidence: 99%
“…1 1 Hz, 1H), 6.97 -6.90 (m, 2H),5.69 (d, J = 5.0 Hz, 1H), 5.67 (d, J = 14.1 Hz, 1H), 5.18 (d, J = 14.1 Hz, 1H), 5.07 (d, J = 5.0 Hz, 1H), 3.83 -3.74 (m, 2H), 3.58 (d, J = 17.8 Hz, 1H), Hz, 1H), 5.09 -5.04 (m, 2H), 3.80 (dd, J = 11.4, 5.6 Hz, 4H), 3.63 -3.53 (m, 1H), 3.14 -3.07 (m, 1H), 2.47 (dq, J = 12.4, 6.2 Hz, 1H), 2.35 (t, J = 7.4 Hz, 2H), 1.90 (dq, J = 12.4, 6.2 Hz, 1H), + , m/z = 577.07023, found 577.07039. The purity of the compound was analyzed by analytical RP-HPLC (Gemini-NX).…”
mentioning
confidence: 99%
“…In conclusion, apart from methylations 45 and benzylations 30 at the phenolic hydroxy groups, the new analogs presented here are, to our knowledge, the first examples of complex semisynthetic derivatives of fidaxomicin obtained via phenolic modifications. Other derivatives recently reported are obtained by semisynthesis, 46 − 48 fermentation, 49 , 50 and fermentation of knockout mutants. 51 54 Based on our predictions of a binding mode of fidaxomicin in a homology model of M. tuberculosis RNAP, which suggested that modifications on the dichlorohomoorsellinic acid would be promising, several analogs have been synthesized and tested for their biological activity and water solubility.…”
mentioning
confidence: 99%